Anchoring Positively Charged Pd Single Atoms in Ordered Porous Ceria to Boost Catalytic Activity and Stability in Suzuki Coupling Reactions. Issue 43 (4th October 2020) - Tao, Xueqin; Long, Ran; Wu, Di; Hu, Yangguang; Qiu, Ganhua; Qi, Zeming; Li, Benxia; Jiang, Ruibin; Xiong, Yujie
Abstract: Single‐atom (SA) catalysis bridging homogeneous and heterogeneous catalysis offers new opportunities for organic synthesis, but developing SA catalysts with high activity and stability is still a great challenge. Herein, a heterogeneous catalyst of Pd SAs anchored in 3D ordered macroporous ceria (Pd‐SAs/3DOM‐CeO2 ) is developed through a facile template‐assisted pyrolysis method. The high specific surface area of 3DOM CeO2 facilitates the heavily anchoring of Pd SAs, while the introduction of Pd atoms induces the generation of surface oxygen vacancies and prevents the grain growth of CeO2 support. The Pd‐SAs/3DOM‐CeO2 catalyst exhibits excellent activity toward Suzuki coupling reactions for a broad scope of substrates under ambient conditions, and the Pd SAs can be stabilized in CeO2 in long‐term catalytic cycles without leaching or aggregating. Theoretical calculations indicate that the CeO2 supported Pd SAs can remarkably reduce the energy barriers of both transmetalation and reductive elimination steps for Suzuki coupling reactions. The strong metal‐support interaction contributes to modulating the electronic state and maintaining the stability of Pd SA sites. This work demonstrates an effective strategy to design and synthesize stable single‐atom catalysts as well as sheds new light on the origin for enhanced catalysis based on the strong metal‐support interactions. Abstract : Pd single atoms are in situ anchored in 3D ordered macroporous ceria. The catalyst exhibits excellent activity and durability toward Suzuki coupling reactions for a broad scope of substrates under the ambient conditions.